THE INTERFERENCE OF FIRST LANGUAGE IN ENGLISH WRITING COMPOSITIONS: A STUDY OF ENGLISH MAJORS AT A LANGUAGE UNIVERSITY = ẢNH HƯỞNG CỦA NGÔN NGỮ THỨ NHẤT - TIẾNG VIỆT ĐỐI VỚI VIỆC VIẾT TIẾNG ANH: MỘT NGHIÊN CỨU VỀ SINH VIÊN CHUYÊN NGÀNH TIẾNG ANH TẠI MỘT TRƯỜNG ĐÀO TẠO NGOẠI NGỮ - Đinh, Bảo Ngọc (2020)
The influence of mother tongue on second language learning has been a significant issue of research into second language acquisition, for mother tongue is an important part of learners’ linguistic background. The present research aims at (1) identifying the errors caused by L1 interference in written compositions, and (2) investigating learners’ perception of the reasons for such problems. The study employs error analysis to categorize errors in 106 written essays and organize interviews with students to explore their perceptions. The collected data from written essays and interviews are analyzed by quantitative and qualitative analysis. The results suggest that verb errors including verb voice and verb number are among the most prominent errors, while calque and collocation errors cause significant problems in lexis aspect. In terms of reasons behind L1 interference errors, two main causes are identified: the difference between Vietnamese and English, and learners’ L1 habit. The study indicates important pedagogical implications for English learning and teaching, which are expected to benefit stakeholders in ESL / EFL contexts.